The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cnma.201900630
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 2D‐ZnS@ZnO Z‐Scheme Heterostructured Nanosheets with a Highly Ordered ZnO Core and Disordered ZnS Shell for Enhancing Photocatalytic Hydrogen Evolution

Abstract: Heterostructure and defects in photocatalyst play highly important role in photocatalysis. Formation of 2D‐ZnS@ZnO Z‐scheme heterostructure and introduction of zinc interstitial defects into ZnO were successfully achieved through a facile in‐situ ion‐exchange hydrothermal approach, and the photocatalysts exhibited high photocatalytic activity for hydrogen evolution. The heterointerface between the highly ordered ZnO core and disordered ZnS shell, and the zinc interstitial, facilitate the transfer and separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Reaction mechanisms of H 2 evolution from scavenger Na 2 S/Na 2 SO 3 solutions containing S 2− , SO 3 2−, or S 2 O 3 2− with PVA-ZnOS hydrogel are proposed in Figure 7. The valence band maximum (VBM) and conduction band minimum (CBM) of ZnO and ZnS were widely reported in the literature [7][8][9][10][11][12][13][14], where the VB of ZnO is lower than that of ZnS and the CB of ZnS is higher than that of ZnO, allowing maximum redox capability of the ZnO/ZnS interface. The presence of Na 2 S/Na 2 SO 3 solution stimulates the H 2 evolution by scavenging photogenerated holes, suppressing the formation of S 2 2− from Na 2 S by SO 3 2− from Na 2 SO 3 [31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reaction mechanisms of H 2 evolution from scavenger Na 2 S/Na 2 SO 3 solutions containing S 2− , SO 3 2−, or S 2 O 3 2− with PVA-ZnOS hydrogel are proposed in Figure 7. The valence band maximum (VBM) and conduction band minimum (CBM) of ZnO and ZnS were widely reported in the literature [7][8][9][10][11][12][13][14], where the VB of ZnO is lower than that of ZnS and the CB of ZnS is higher than that of ZnO, allowing maximum redox capability of the ZnO/ZnS interface. The presence of Na 2 S/Na 2 SO 3 solution stimulates the H 2 evolution by scavenging photogenerated holes, suppressing the formation of S 2 2− from Na 2 S by SO 3 2− from Na 2 SO 3 [31].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of Na 2 S/Na 2 SO 3 solution stimulates the H 2 evolution by scavenging photogenerated holes, suppressing the formation of S 2 2− from Na 2 S by SO 3 2− from Na 2 SO 3 [31]. When UV light was radiated, ZnO/ZnS photocatalyst was activated by Z-scheme heterojunction, where excited electrons at the CB of ZnO recombined with holes at the VB of ZnS [8,11,14]. The accumulation of holes at the VB of ZnO and electrons at the CB of ZnS reduced the recombination between electrons and holes, enhancing the photocatalytic reaction [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many semiconductor materials including TiO 2 , Bi 2 WO 6 , CeO 2 , ZnO, etc. have been widely investigated as photocatalysts for CO 2 photoconversion [2–5] . Though great progress has been achieved, there are still several issues to be overcome urgently.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, scientists have been committed to exploring renewable energy sources due to the increasing demand for fossil fuels and worsening environmental conditions [1–5] . As we know, H 2 energy, one of the cleanest energy sources, has been widely considered as a promising candidate to fossil fuel for solving the problem of energy crisis [6–10] . Since Fujishima and his colleagues first reported that TiO 2 electrode achieved photoelectrochemical water splitting in 1972, the photocatalytic H 2 production based on semiconductor photocatalysts has been taken for a prospective method to convert solar energy to chemical fuels [11–13] .…”
Section: Introductionmentioning
confidence: 99%